A different expression of the Weil–Petersson potential on the Quasi-Fuchsian deformation space - Teo, Lee-Peng (Springer Netherlands, 2005)
We extend a definition of the Weil-Petersson potential on the universal Teichmuller space to the quasi-Fuchsian deformation space. We prove that up to a constant, this function coincides with the Weil-Petersson potential on the quasi-Fuchsian deformation space. As a result, we prove a lower bound for the potential on the quasi-Fuchsian deformation space.